Dynamical regimes of kinematic vortices in the resistive state of a mesoscopic superconducting bridge - Presotto, Alice [UNESP]; Sardella, Edson [UNESP]; Malvezzi, André Luiz [UNESP]; Zadorosny, Rafael [UNESP] (IOP Publishing, 2020)
In this work, we studied the dynamics of the kinematic vortices (kV) in a mesoscopic superconductor under the influence of external applied magnetic fields (H) and transport currents (J tr). A J tr(H) phase diagram is determined. We show that the vortex dynamics are profoundly affected by the presence of constrictions and by H. We find that between the Meissner and normal states, the resistive state is comprehended by three distinct states. One of these states is a kinematic vortex-antivortex pair for low values of H. For moderate values of fields, the kV state is unpaired and only a single kinematic vortex exists. In the high field regime, the kinematic vortex becomes an Abrikosov-like state with a lower velocity. It was also shown that for tenths of picoseconds, a surface barrier effect acts over the instantaneous velocity of the kV.
Keywords: bridge; dynamical regimes; kinematic vortices; mesoscopic superconductor; TDGL; voltage oscillations